Gut microbiota therapy for nonalcoholic fatty liver disease: Evidence from randomized clinical trials - Han, Ting-Rui; Yang, Wen-Juan; Tan, Qing-Hua; Bai, Shuai; Zhong, Huang; Tai, Yang; Tong, Huan (Frontiers in Microbiology, 2023)
Non-alcoholic fatty liver disease (NAFLD) has a high prevalence worldwide, but there is no medications approved for treatment. Gut microbiota would be a novel and promising therapeutic target based on the concept of gut-liver axis in liver disease. We reviewed randomized controlled trials on gut mocrobiota therapy in NAFLD in this paper to evaluate its efficacy and plausibility in NAFLD.